Використання бездротових технологій для передачі даних з IoT на локальний сервер - Подгорнова, А. Д. (ХНУРЕ, 2024)
This study delves into the application of wireless technologies for transmit ting data from Internet of Things (IoT) devices to local servers. Focused on enhancing security, reliability, and data processing efficiency in IoT systems, the project utilizes an Arduino board with the ESP8266 WiFi module (WeMos D1) to wirelessly transmit data to a local server. By reducing delays, increasing data security, and complying with local regulations, the approach aims to improve the overall reliability and security of IoT systems. The use of Wi-Fi as a wireless data transmission standard provides a stable and high-speed connection within home or office networks, facilitating effective data exchange between smart de vices and the local server.
Keywords: передача даних на локальний сервер; локальний сервер